2010
DOI: 10.5205/reuol.1359-10501-1-le.0501201014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk for wheezing at home by caregivers

Abstract: Objective: to investigate the ability of caregivers in identification of risk factors for wheezing existing residences of children wheezing and/or asthmatic children under five years. Method: this about an exploratory, cross-sectional study, from quantitative approach, performed with caregivers of children wheezing and/or asthma assisted in two Family Health Units in Jaboatão dos Guararapes city, Pernambuco, Brasil. Data were collected with the use of two techniques: interviews and field observation after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…21 In a study, the presence of birds after birth showed to be significant with regard to the onset of episodes of recurrent wheezing (p < 0.03). 3 In another study, there was no association between wheezing in the first year of life and history of rhinitis and dermatitis in the family, smoking by other family members, intake of processed foods by the nursling, maternal education level, number of siblings, etc. 22 Recurrent wheezing is a public health problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In a study, the presence of birds after birth showed to be significant with regard to the onset of episodes of recurrent wheezing (p < 0.03). 3 In another study, there was no association between wheezing in the first year of life and history of rhinitis and dermatitis in the family, smoking by other family members, intake of processed foods by the nursling, maternal education level, number of siblings, etc. 22 Recurrent wheezing is a public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…1 Wheezing poses a great burden of care to parents, as well as to the health care system. 2 In the first year of life, most consultations and hospitalizations in pediatrics is due to wheezing 3 , and recurrent wheezing results in an important increase in the use of health resources and a high economic cost, besides a compromised quality of life of patients and relatives. 4 The presence of recurrent wheezing in the first year of life may indicate the emergence of bronchial asthma in children.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, among these adaptations, it was mentioned removing carpets, curtains, plants, pets, intensifying domestic hygiene as the most recommended measure for crisis prevention and ensuring safety and comfort. 20 Another care strategy used by the family is the inclusion of children with chronic disease in their own care. The knowledge that children with chronic diseases have about their infirmity and self-care requirements related to them, can give them basis for the continuation of adequate therapy and prevention of recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%